Effect of Different Feeding on Feed Conversion and Growth of Common Carp (Cyprinus carpio) in Floating Net Cage Culture at Jatiluhur Dike - Utomo, N.B.P; Kumalasari, F.; Mokoginta, I. (Indonesian Society of Scientific Aquaculture (ISSA), 2005)
This experiment was conducted to evaluate the effectiveness of two feeding methods commonly used in cage culture of carp Cyprinus carpio at Jatiluhur Lake, Purwakarta. Common carp in mean weight of 24.29±4.29 gram were reared in floating net cage 7×7×3 m3, for 70 days rearing. Fish were fed on a commercial diet containing 30% protein at 5 times daily. Experimental treatment was feeding technique, i.e., by 6% of body weight, and at satiation for the second treatment. The results showed that the application of